Development of an Android-Based E-Module to Enhance Solo Puteri Bridal Makeup Competence - Mu’daim, Syarifah; Widjanarko, Dwi; Kusumastuti, Adhi (Universitas Negeri Semarang, 2023)
Currently, the instructional videos on Solo Puteri bridal makeup, sourced by instructors from YouTube, only cover certain aspects of the curriculum for Solo Puteri bridal makeup courses. Educators often face time constraints when creating their own audiovisual learning materials. This study aims to (1) assess the feasibility of an Android-based e-module using App Inventor for Solo Puteri bridal makeup competence; (2) evaluate the effectiveness of the Android-based e-module using App Inventor for Solo Puteri bridal makeup competence; (3) determine the practicality of the Android-based e-module using App Inventor for Solo Puteri bridal makeup competence.The research model utilized in this study is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The development research subjects consist of 12 active students majoring in Makeup at AKS Ibu Kartini Semarang. Data analysis methods include the Content Validity Index (CVI) and Percentage of Agreement (PA) for feasibility testing, t-tests and N-gain for effectiveness testing, and reproducibility coefficient (Kr) and scalability coefficient (Ks) for practicality testing.The study results are as follows: (1) The product developed is an e-module for Solo Puteri bridal makeup; (2) The product is deemed feasible based on a Content Validity Index (CVI) score of 1 from media experts, a Percentage of Agreement (PA) of 100%, and a CVI score of 1 and PA of 100% from material experts; (3) Product trials show an effectiveness level of 0.67, with an effectiveness percentage of 67.36%, indicating a moderate effect and that the e-module is reasonably effective; (4) The reproducibility coefficient (Kr) is 94% and the scalability coefficient (Ks) is 72%, suggesting that the e-module for Solo Puteri bridal makeup is practical